Mechanical and bond properties of FRP anchor spikes in concrete and masonry blocks. (1st January 2018) - Carozzi, Francesca Giulia; Colombi, Pierluigi; Fava, Giulia; Poggi, Carlo
Abstract: Fibre Reinforced Polymer (FRP) materials are extensively used to retrofit masonry and reinforced concrete structures. Failure occurs in most cases due to composite debonding from the substrate. The use of FRP anchor spikes was thus proposed to reduce premature debonding failure. In this work, the results of an extensive experimental program on the bond behaviour between the FRP anchor spikes and the substrate are first presented. They include both the mechanical characterization of carbon and glass FRP anchor spikes and pull-out tests from concrete and masonry blocks. In pull-out specimens, FRP anchor spikes are embedded into the block (embedded anchor spikes) or fanned-out on the substrate surface (fanned-out anchor spikes) with an epoxy resin. For different specimen configurations and materials, the bond behaviour of the FRP anchor is analysed. The mostly observed failure modes were the tensile failure of the anchor spikes, the debonding of the anchor spikes from the substrate or a combination of both. Nonlinear finite element simulations were finally performed to understand the bond behaviour between FRP anchors spikes and concrete substrate.